2008
DOI: 10.1172/jci35432
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cell transplantation can ameliorate the phenotype of a mouse model of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA), a motor neuron disease (MND) and one of the most common genetic causes of infant mortality, currently has no cure. Patients with SMA exhibit muscle weakness and hypotonia. Stem cell transplantation is a potential therapeutic strategy for SMA and other MNDs. In this study, we isolated spinal cord neural stem cells (NSCs) from mice expressing green fluorescent protein only in motor neurons and assessed their therapeutic effects on the phenotype of SMA mice. Intrathecally grafted NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 60 publications
1
97
1
5
Order By: Relevance
“…Several previous studies, including ours, have reported strong up-regulation of Cdkn1a/p21, a cyclin-dependent kinase inhibitor and mediator of cell cycle arrest downstream of p53, as well as other regulators of cell cycle and DNA repair in SMA models (6,19,(23)(24)(25). Whereas the Cdkn1a up-regulation has been attributed to a p53-independent stabilization of Cdkn1a transcript in the absence of SMN protein (26,27), few other gene expression changes can be explained by such posttranscriptional regulation.…”
Section: Significancementioning
confidence: 53%
“…Several previous studies, including ours, have reported strong up-regulation of Cdkn1a/p21, a cyclin-dependent kinase inhibitor and mediator of cell cycle arrest downstream of p53, as well as other regulators of cell cycle and DNA repair in SMA models (6,19,(23)(24)(25). Whereas the Cdkn1a up-regulation has been attributed to a p53-independent stabilization of Cdkn1a transcript in the absence of SMN protein (26,27), few other gene expression changes can be explained by such posttranscriptional regulation.…”
Section: Significancementioning
confidence: 53%
“…ALDHbr cells were cultured under conditions that promoted formation of motor neurons and transplanted i.t. into mouse models of spinal motor atrophy [48,49]. Both transplanted neurons and uncultured ALDHbr cells migrated to ventral horns and established functional neuromuscular junctions.…”
Section: Aldhbr Cells From Neural Tissuementioning
confidence: 99%
“…Uncultured, freshly isolated ALDHbr cells also improved the disease progression and secreted several of protective cytokines, although not as much as the cultured cells. Corti et al [49] suggested that isolating ALDHbr cells and culturing them in the absence of the inhibitory effects of spinal cord glial cells promotes the development of cells that can produce neuroprotective cytokines. This recalls the effect of enriching ALDHbr cells on efficacy of human bone marrow in the hind limb ischemia model discussed above.…”
Section: Aldhbr Cells From Neural Tissuementioning
confidence: 99%
“…Cellular therapies, however, have been examined in mouse models of SMA, where grafting of ES derived NPCs protected MNs from degeneration and improved survival. 37 The correction of SMN gene, using singlestranded oligonucleotide, was shown to restore the SMN gene profile in neurons derived from SMA-iPSC, converting SMN2 in SMN1. 38 It is possible that for SMA, transient rescue of the developmental loss of SMN may be sufficient to confer efficacy, which may not be the case for other neurodegenerative diseases where long-term degeneration of the transplanted cells is a valid concern.…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%